2022
DOI: 10.1371/journal.pone.0259190
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of ZnO nanoparticles using Acacia arabica leaf extract and their antibiofilm and antioxidant potential against foodborne pathogens

Abstract: Emergence of multidrug resistant pathogens is increasing globally at an alarming rate with a need to discover novel and effective methods to cope infections due to these pathogens. Green nanoparticles have gained attention to be used as efficient therapeutic agents because of their safety and reliability. In the present study, we prepared zinc oxide nanoparticles (ZnO NPs) from aqueous leaf extract of Acacia arabica. The nanoparticles produced were characterized through UV-Visible spectroscopy, scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 56 publications
1
19
0
1
Order By: Relevance
“…However, few studies compared these two means of synthesis, and some of them showed evidence that green synthesized ZnNPs even had lower antimicrobial effect ( 77 , 78 ). Moreover, disadvantages of the green synthesis include poor control of NPs formation, difficulty in large-scale production and differences in compound composition in plant extracts ( 79 ). Similar discussion has been held regarding to efficiency of modified and doped ZnNPs.…”
Section: Znnps As a Prospective Antimicrobial Agentmentioning
confidence: 99%
“…However, few studies compared these two means of synthesis, and some of them showed evidence that green synthesized ZnNPs even had lower antimicrobial effect ( 77 , 78 ). Moreover, disadvantages of the green synthesis include poor control of NPs formation, difficulty in large-scale production and differences in compound composition in plant extracts ( 79 ). Similar discussion has been held regarding to efficiency of modified and doped ZnNPs.…”
Section: Znnps As a Prospective Antimicrobial Agentmentioning
confidence: 99%
“…The average hydrodynamic diameter of the bio-prepared ZnO-NPs was assessed using a dynamic light scattering technique [ 44 ]. Moreover, the surface charge of ZnO-NPs was appraised using zeta potential examination.…”
Section: Resultsmentioning
confidence: 99%
“…The inoculation culture plates were kept at 4 °C for 5 h before being cultivated for 48 h at 37 °C in an incubator. The inhibitory zones that emerged after incubation were assessed 95 .…”
Section: Methodsmentioning
confidence: 99%